The merchant of Venice - Shakespeare, William; Warfield, David, 1866-1951.; Belasco, David, 1853-1931.; Shakespeare, William, 1564-1616.; National Theatre Corporation (Washington, D.C.); Theater Playbills and Programs Collection (Library of Congress) (Cambridge : University Press., 1968)
National Theatre, direction W.H. Rapley, business management W.H. Fowler. David Belasco presents Mr. Warfield as Shylock in Wm. Shakespeare's "The Merchant of Venice." Play produced under the personal direction of Mr. Belasco, the scenic investiture by Ernest Gros.
In: American theater programs of the late 19th and 20th centuries (Library of Congress).
Keywords: Theater programs -- Washington (D.C.); Theater programs -- 1922.